Notifikasi Gangguan Penyulang pada Distribusi Primer - Rahman Syamsu Ganda; Nina Paramytha (Universitas Batanghari Jambi, 2023)
The network system is a very vital network in the flow of electrical energy, therefore it is very informed in real time when there is a disturbance in electrical transmission so that electrical energy is continuous. When there is a disturbance in the electricity network, there is a notification in real time, so the officer will quickly find out if there is a disturbance. Disturbances that occur in the field cannot be predicted because of the long network and different fields, so a prototype is designed to provide notifications when a disturbance occurs in real time using a current sensor using an acs712 current sensor as a current reader and a 004t pzem voltage sensor. Utilization of the esp32 module serves to send notifications to officers via the telegram application.